Implementation Merdeka Curriculum Learning Islamic Religious Education and Ethics at Vocation School - Burhanuddin, Hamam; Khi’Mah, Fitrotul; Fauziyah, Zumrotul (TA'DIBUNA: Jurnal Pendidikan Agama Islam, 2024)
The purpose of the article is to describe the application of the independent curriculum for learning Islamic Religius Education and character in class X at SMKN 2 Bojonegoro and analyze the supporting and inhibiting factors. using descriptive qualitative research, carried out June 12-July 8 at SMKN 2 Bojonegoro, research subjects are class X students, class X Islamic Religious Education and character teachers and head curriculum, data sources from primary and secondary data, this research instrument from observation, interview and documentation guidelines. Data were collected according to the research objectives, namely describing and analyzing. The data obtained from observations, interviews and documentation were then analyzed descriptively. The results of this article study are: (1) The implementation of the independent curriculum for learning and character in class X Islamic Religious Education at SMKN 2 Bojonegoro has three stages, namely planning, implementation, assessment and evaluation. (2) Supporting factors: superior human resources of teachers and students, leadership readiness of the head and school committee, adequate learning facilities. Inhibiting factors: the environment and background of students and the lack of family support for students.